Legal View on the Definition of Advocates as Law Enforcement Officers from a Positive Law Perspective - Muhammad Taufiq (JURNAL ILMIAH LIVING LAW, 2026)
This study examines the legal perspective on the profession of advocates as law enforcers in Indonesia, focusing on the inconsistency of referring to advocates as law enforcement officers, similar to judges, prosecutors, and police. Based on Law Number 18 of 2003 concerning Advocates, Article 5 paragraph (1), advocates have the status of law enforcers who are free, independent, and guaranteed by law, but do not have the same characteristics and authority as law enforcement officers. Advocates play a crucial role in providing legal services, including consultation, assistance, and defense, for the interests of clients, without the bureaucratic hierarchy and authority that often accompany detention, prosecution, or legal decision-making. This study uses a normative juridical method by analyzing laws and regulations, expert opinions, and legal literature. The results of the study indicate that advocates play a crucial role in maintaining justice and protecting human rights within the justice system, encompassing both criminal and civil matters, with the principles of independence and immunity that are recognized nationally and internationally. However, referring to advocates as law enforcement officers is inappropriate due to differences in duties, functions, and independence. This study recommends reaffirmation in regulations to clarify the status of advocates as independent law enforcers, as well as increasing public understanding to strengthen the integrity of the advocate profession in supporting a fair justice system in Indonesia.